Modeling the Number of Infant Mortality in East Lombok using Geographically Weighted Poisson Regression - Baiq Urfa Justitiaski; Nurul Fitriyani; Syamsul Bahri (University of Mataram, 2022)
Infant mortality is death that occurs at the age of 0 to 1 year. According to the Provincial Health Office, East Lombok is the district with the largest infant mortality rate in NTB. Several factors influence infant mortality: childbirth with medical assistance, low birth weight, health facilities, health workers, and exclusive breastfeeding. These factors have a spatial influence because each region has different geographical, socio-cultural, and economic conditions. Therefore, the method that can be used is GWPR because it can model data with the response variable with a Poisson distribution and pay attention to location or spatial aspects. This study aims to determine the infant mortality model in East Lombok using Geographically Weighted Poisson Regression (GWPR) and to determine the factors that significantly influence the number of infant deaths in East Lombok. Based on the research conducted showed that low birth weight is the only factor that significantly affected infant mortality in 8 sub-districts, including Keruak, Sakra, West Sakra, East Sakra, Terara, Sukamulia, Selong, and Labuhan Haji. The model obtained gives a good estimator, with an R^2 value of 76,44%.